2001
DOI: 10.1128/jb.183.17.5074-5081.2001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Structural Organization of the Aminophenol Catabolic Operon and Its Implication for Evolutionary Process

Abstract: The aminophenol (AP) catabolic operon in Pseudomonas putida HS12 mineralizing nitrobenzene was found to contain all the enzymes responsible for the conversion of AP to pyruvate and acetyl coenzyme A via extradiol meta cleavage of 2-aminophenol. The sequence and functional analyses of the corresponding genes of the operon revealed that the AP catabolic operon consists of one regulatory gene, nbzR, and the following nine structural genes, nbzJCaCbDGFEIH, which encode catabolic enzymes. The NbzR protein, which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 54 publications
0
22
1
Order By: Relevance
“…1D) (12), and AmnR, a repressor for the 2-AP pathway (in analogy to NbzR, a transcriptional repressor for the nbz genes of which the effector compound is unknown) (Fig. 1E) (45). In contrast to what we expected, we observed that the clc genes were induced in the presence of not only 3-CBA and 4-chlorobenzoate but also anthranilate, benzoate, and salicylate.…”
Section: Resultscontrasting
confidence: 55%
See 1 more Smart Citation
“…1D) (12), and AmnR, a repressor for the 2-AP pathway (in analogy to NbzR, a transcriptional repressor for the nbz genes of which the effector compound is unknown) (Fig. 1E) (45). In contrast to what we expected, we observed that the clc genes were induced in the presence of not only 3-CBA and 4-chlorobenzoate but also anthranilate, benzoate, and salicylate.…”
Section: Resultscontrasting
confidence: 55%
“…1E) consisted of a complete catabolic operon for 2-AP degradation via meta cleavage (31) that was similar to the amn gene cluster of Pseudomonas sp. strain AP-3 (61,62) and to parts of the nitrobenzene pathway genes of Pseudomonas fluorescens strain KU-7 (41) and P. putida HS12 (45). The amn operon on the clc element is formed by a putative transcriptional repressor (amnR, ORF22813), a ferredoxin-like protein (ORF23526), and eight amn genes, amnBACDFEHG ( Table 1. 1E).…”
Section: Resultsmentioning
confidence: 99%
“…The nbz operon for aminophenol degradation on plasmid pNB1 in P. putida HS12 is regulated by NbzR, a MarR-type repressor protein (176). The chemical inducer for the pathway has not been identified, and it was proposed that another trans-acting factor might be involved in regulating pathway expression.…”
Section: Marr-type Regulatorsmentioning
confidence: 99%
“…Instead, the protein possesses a putative leucine zipper motif (which is absent in other family members), which is thought to be responsible for the NbzR dimerization and DNA binding. Hence, Park and Kim suggested that the poor HTH motif of NbzR perhaps does not contribute to DNA binding (176). MarR-type regulators controlling catabolic operons are relatively small proteins.…”
Section: Marr-type Regulatorsmentioning
confidence: 99%
See 1 more Smart Citation